INFORMATION GOVERNANCE AND ACCOUNTABILITY TO IMPROVE FUNDING PERFORMANCE, DIGITAL TRANSPARENCY AND CSO SUSTAINABILITY IN INDONESIA - Sony; Henryanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores how information governance and financial accountability shape funding performance and the long-term sustainability of Civil Society Organizations (CSOs) in Indonesia. This study employed a mixed-methods approach to collect data from 709 Civil Society Organizations (CSOs) across 34 provinces in Indonesia. Data were obtained through surveys, analysis of digital platforms, and structured interviews, allowing for a comprehensive understanding of CSO practices and challenges. The framework examines legal compliance, digital visibility, and accountability systems. Findings reveal a critical gap: 84% of CSOs have legal recognition, 93% hold tax IDs, and only 44% regularly undergo audits. Moreover, 86% depend heavily on grants and donations, and just 17% actively use integrated digital platforms. This misalignment between formal compliance and strategic accountability risks donor confidence and long-term viability. The study proposes a diagnostic model interlinking governance, digital engagement, and funding strategy. Practical recommendations include improving audit practices, advancing digital transparency, and encouraging innovative, diversified funding approaches. The insights contribute to ongoing efforts by policymakers, donors, and CSOs to cultivate more transparent, resilient, and accountable nonprofit ecosystems.